2007
DOI: 10.1667/rr0735.1
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Magnetic Resonance Spectroscopy Reveals a Potential Relationship between Radiation-Induced Changes in Rat Brain Metabolites and Cognitive Impairment

Abstract: To test the efficacy of magnetic resonance spectroscopy (MRS) in identifying radiation-induced brain injury, adult male Fischer 344 rats received fractionated whole-brain irradiation (40 or 45 Gy given in 5-Gy fractions twice a week for 4 or 4.5 weeks, respectively); control rats received sham irradiation. Twelve and 52 weeks after whole-brain irradiation, rats were subjected to high-resolution MRI and proton MRS. No apparent lesions or changes in T(1)- or T(2)-weighted images were noted at either time. This i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
62
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 44 publications
9
62
4
Order By: Relevance
“…The Cramer-Rao Lower Bound estimating produced by the LCModel avoids extensive examination of each spectroscopic image and helps reject low-quality spectra (Fig 4). 46 Studies 47,48 have suggested that the coefficient of variation of absolute substance content calculated by the LCModel is lower than that for the ratio of metabolites.…”
Section: Figmentioning
confidence: 99%
“…The Cramer-Rao Lower Bound estimating produced by the LCModel avoids extensive examination of each spectroscopic image and helps reject low-quality spectra (Fig 4). 46 Studies 47,48 have suggested that the coefficient of variation of absolute substance content calculated by the LCModel is lower than that for the ratio of metabolites.…”
Section: Figmentioning
confidence: 99%
“…They suggested a potential relationship between RT-induced brain injury and neurocognitive dysfunction (Fig. 17) (Atwood et al 2007). …”
Section: Mr Proton Spectroscopymentioning
confidence: 99%
“…Significant metabolites changes (c) and reduced cognitive function (d) after 52 and 54 weeks of whole brain irradiation, respectively (*, **, and, *** represent statistically significant results; p-values are less than 0.01). Reproduced with permission from Atwood et al (2007) 5.3 PET A study from M.D. Anderson reported hepatic radiation injury using FDG-PET in patients with distal esophageal cancer treated with chemoradiation.…”
Section: Mrimentioning
confidence: 99%
“…As mentioned by Jeraj and colleagues, there is a need to develop non-invasive functional and molecular imaging that is able to identify early imaging manifestations of IR-related effects (i.e., before clinical manifestations) in order to propose candidate mitigators [115]. Magnetic resonance spectroscopy (MRS) recently showed promising imaging results after fractionated brain irradiation in rats [116]. The particularity of this functional imaging is its capacity to identify metabolic distribution in the brain.…”
Section: Prospects and Conclusionmentioning
confidence: 99%